2021
DOI: 10.3389/fpsyg.2021.622493
|View full text |Cite
|
Sign up to set email alerts
|

By the Book or Out of the Box? Top Decision Maker Cognitive Style, Gender, and Firm Absorptive Capacity

Abstract: Despite scholars’ early emphasis on the role people play in fostering firms’ absorptive capacity (AC), research has not deeply explored the individual-level antecedents of this important capability. We draw on adaptive-innovative theory to explain how top decision makers’ cognitive styles can influence the degree to which their firms develop AC. Top decision makers who have high adaptive cognitive style prefer to adhere to existing norms, follow established procedures, and rely on current knowledge, and we arg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 107 publications
(159 reference statements)
0
8
0
Order By: Relevance
“…Organizations can attain competitive advantage by using and implementing the instrument style for making decisions in their organizations (Vranic et al, 2019;Oladotun, 2020). Cognition would help managers, leaders and organizations to make quick decisions saving time and cost moreover, it was revealed that decision making and especially cognitive styles have positive and negative effect on the leaders and followers organizational citizenship behavior (Armstrong & Qi, 2020;Costantini, Kwong, Smith, Lewcock, Lawlor, Moran , Tilling , Golding & Pearson 2021;Pryor, Hirth & Jin 2021). This study extended the body of knowledge through lens of cognitive style theories and decision making theories.…”
Section: Discussionmentioning
confidence: 71%
“…Organizations can attain competitive advantage by using and implementing the instrument style for making decisions in their organizations (Vranic et al, 2019;Oladotun, 2020). Cognition would help managers, leaders and organizations to make quick decisions saving time and cost moreover, it was revealed that decision making and especially cognitive styles have positive and negative effect on the leaders and followers organizational citizenship behavior (Armstrong & Qi, 2020;Costantini, Kwong, Smith, Lewcock, Lawlor, Moran , Tilling , Golding & Pearson 2021;Pryor, Hirth & Jin 2021). This study extended the body of knowledge through lens of cognitive style theories and decision making theories.…”
Section: Discussionmentioning
confidence: 71%
“…Fierce competitive pressure forces firms to make change and occupy more market shares [33]. These firms which prefer to adopt innovative technology enhances the flexibility and stability of operations, and integrates differentiation into firms' services and products [34], which updates the industry standards, elevates industry barriers and establishes new industry benchmark of being the leader [21]. So, the hypothesis is proposed: Hypothesis 1.…”
Section: Plos Onementioning
confidence: 99%
“…Individuals with adaptive cognitive styles follow rules and use more traditional methods to solve problems. Leaders with adaptive cognitive styles often refer to experience, follow existing procedures to complete work or solve problems and maintain high stability and accuracy in the work (Isaksen et al, 2003;Kahai et al, 2013;Pryor et al, 2021). Compared to leaders with innovative cognitive styles, they are more conservative and less aggressive, as well as less likely to engage in entrepreneurial leadership behavior.…”
Section: Cognitive Style and Entrepreneurial Leadershipmentioning
confidence: 99%
“…They are not stuck within existing rules, which is conducive to grasping potential business opportunities and breaking existing patterns (Frederiks et al, 2018). Further, they always seek innovative practices, are good at using creative ideas to deal with problems, drive team members to learn new things and actively develop solutions in the face of sudden changes in the external environment (Pryor et al, 2021;Dewberry et al, 2013;Li and Li, 2012). The biggest challenge faced by entrepreneurial leaders is convincing subordinates to get rid of traditional constraints and the sense of occupational safety to innovate or start a business (Iqbal et al, 2022;Lingo, 2020).…”
Section: Cognitive Style and Entrepreneurial Leadershipmentioning
confidence: 99%